2000
DOI: 10.1038/sj.sc.3101095
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with thoracic spinal cord injury, lesion level and rotator cuff disorders

Abstract: Background:The study was concerned with the secondary functional compromise persons with long-term paraplegia contend with, that has been shown to be associated with wheelchair use. Of particular interest was the relationship between the level of thoracic spinal cord injury (SCI) and factors predisposing to rotator cu disorders (RCD), one of the most common upper extremity musculoskeletal complications linked with long-term SCI. Disorders of these peri-articular structures have previously been associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 14 publications
1
46
0
1
Order By: Relevance
“…Impairment of postural control has been associated with a greater anterior displacement of the trunk during static balance and scapular protraction during dynamic situations. 5 Koo et al 6 have demonstrated that patients with paraplegia tend to move their pelvis backward and incline their trunk forward, thus adopting a relaxed posture when sitting on foam seat, whereas wheelchair air seat (Roho cushion) seems to help in maintaining a correct posture. However, Aissaoui et al 7 noted that generic contoured foam promoted greater stability during a reaching task than flat foam and Roho cushion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of postural control has been associated with a greater anterior displacement of the trunk during static balance and scapular protraction during dynamic situations. 5 Koo et al 6 have demonstrated that patients with paraplegia tend to move their pelvis backward and incline their trunk forward, thus adopting a relaxed posture when sitting on foam seat, whereas wheelchair air seat (Roho cushion) seems to help in maintaining a correct posture. However, Aissaoui et al 7 noted that generic contoured foam promoted greater stability during a reaching task than flat foam and Roho cushion.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with thoracic SCI, both high (T2-T8) and low spinal cord injury (T9-T12), have difficulty in maintaining their seated position without compensation and misalignment of their skeletal structure, as the muscle group responsible for posture maintenance [2][3][4] and pelvic stability 5 is lost. Impairment of postural control has been associated with a greater anterior displacement of the trunk during static balance and scapular protraction during dynamic situations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, WCBPs make ample use of the upper limb and trunk muscles both for wheelchair propulsion and for throwing the ball during the matches [23][24][25] . Some of these muscles involved in the stabilization, positioning, and execution of upper limb; trunk movements also act as the accessory muscles facilitating the inspiratory and expiratory processes.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study are in agreement with those described by Moreno 12 and could also be attributed to the previously described training of the accessory muscles during the WCB practice. Moreover, some of scapular girdle muscles act in upper limb movement and stabilization and serve as accessory muscles in the forced inspiration process [23][24][25]29 . The constant utilization of these muscles during the WCB training may have resulted in adaptations in their functions and morphologies, which culminated in a greater capacity to generate force.…”
Section: Discussionmentioning
confidence: 99%
“…Waring & Maynard (1991) reported 23% of this group of patients still had the same or worse shoulder pain at the 6 months discharge. Regardless of the level of spinal cord injury or the result of functional movement patterns, muscle imbalances around the shoulder joint are thought to contribute to shoulder disorders in wheelchairs users (Sinnott et al, 2000).…”
Section: Specific Target Groupsmentioning
confidence: 99%